PENGARUH KOMITMEN KERJA TERHADAP PRODUKTIVITAS KERJA PADA GURU SMP NEGERI KECAMATAN KEMAYORAN JAKARTA PUSAT PROVINSI DKI JAKARTA - Boma Jonaldy Tanjung; Deni Indra Purnama Koto (Aliansi : Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine: 1) the effect of commitment on employee work productivity; 2) the effect of work experience on employee work productivity; 3) which influence is more dominant between work commitment and work experience on employee work productivity. This research is a descriptive associative research with hypothesis testing. The population in this study was a sample of 60 public junior high school teachers in Kemayoran, Central Jakarta, with a saturated sample technique. The data collection technique used a questionnaire and tested its validity and reliability. The data analysis technique used was the F test, t test and R2 test. The results of this study are that work motivation and work experience together have a positive effect on teacher work productivity. This is evident from the results of the F test which obtained Fcount of 36,956 Ftable of 3,159 and a significant value of 0.000 0.05. Work motivation has a positive effect on teacher work productivity. This is evident from the results of the t test which obtained tcount X1 = 3.584 t table of 1.671 and a significant value of 0.001 0.05. Work Experience has a positive effect on Employee Work Productivity. This is evident from the results of the t test which obtained t count X2 = 3.294 t table of 1.671 and a significant value of 0.002 0.05. From these results Work Motivation has a greater (dominant) influence on Employee Productivity. This is evident from the results of the t test which obtained t count X1 is greater than t count X2, namely 3.584 3.294.